Methods in World History: A Critical Approach. (Kriterium, 2016)
"Interest in world history has never been greater--both among historians and the reading public. Globalization has coaxed historians out of their fixation on all things national, which has characterized historical research since the nineteenth century. But with this new global field of research has come new methodological problems. It is high time that these problems were tackled, if only to develop methods to ensure that world-historical research strives for the same high quality and standards as any other field of historical study. This book addresses all these problems in detail, with a particular emphasis on solutions. The contributors discuss how the progress made in the sciences, which offer unique access to new types of source material, can best be used by the historians of global processes. These are sources that demand an awareness of both their advantages and their drawbacks. The same is true of the secondary sources, which are the basis of most world-historical overviews and syntheses. Primary and secondary sources alike require shrewd handling in a way not seen before. Similarly, the calculations and comparisons essential to world history must be harmonized, and historians have to acknowledge that the information they are working from is often of variable quality and detail. Linguistic and cultural differences must also be analysed systematically whenever historians seek the recurring traits in human history, much as they must be alert to the strong ideological interests that all too often distort scholarly results. Solutions to these and the other methodological problems are hammered out in this book. Whether researchers, students, or interested readers, anyone keen to sharpen their critical thinking about world history will find there is much to take away from this book.